PENGARUH KARAKTERISTIK CURAH HUJAN TERHADAP KESTABILAN LERENG - Agustina, Dian Hastari (JURNAL DIMENSI, 2013)
Landslide is one of accident that often occur in natural or artificial slope.  Landslide often takes place on the rainy season.  Many landslides that occur on rainy season were caused by an increase in pore water pressure.  This, results in  decreasing the shear strenght then failures occur.  This research was done in Kalibawang irrigation channel in Kulon Progo, especially in km.7.8.            This research was done in two steps.  The first step was to analyse ground water slope behavior (hidrological condition) in respon to the rainfall infiltration by hidrology modelling, from initial condition without rain and then continuous with raining condition.  The rainfall intensities applied for modelling were intensity 60 mm/hour and 5 mm/hour respectively.  The next step was to identify influence of the rain models in slope condition that result in decrease slope stability.            This research result is the decrease of slope stability is influence by intensity and duration of the rain.  Rain infiltration  caused to the change of suction that also influenced to the slope stability.  From the analyses all of the rainfall was potential to decrease matrix suction and slope stability, but the most decrease of slope stability was caused of rainfall with intensity 5mm/hour for 12 hours than rainfall with intensity 60mm/hour for an hour.